Can Electric Vehicle Charging Stations Be Carbon Neutral With Solar Renewables? - Demirci, Alpaslan; Ozturk, Zafer; Terkes, Musa; Tercan, Said Mirza; Yumurtaci, Recep; Cali, Umit (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
In line with sustainable energy and environmental targets, the share of electric vehicles in the automobile market is expected to reach 80%. On the other hand, unplanned electric vehicle charging station installation for EV charging demands and high dependency rates on the distribution grid may adversely affect grid reliability, energy costs, and environmental targets. This article investigates whether electric vehicle charging stations can achieve carbon neutrality through strategic techno-economic integration with solar renewables. Furthermore, an exhaustive analysis investigated achieving carbon neutrality via integrating energy storage systems with photovoltaics, factoring in investment costs and carbon taxes. The findings indicate a significant potential for reducing grid dependency by up to 54.3%. Implementing a more stringent carbon tax has facilitated a notable enhancement in energy storage system capacity, increasing the self-consumption rate by 72% and declining carbon emissions by 25.55%. Self-consumption decreases by 30% during high charging demand in the morning and evening hours, leading to increased dependency on the grid and emphasizing the critical requirement for improved strategies to reduce carbon emissions. Despite the significant investment required for energy storage systems, a gradual increase in carbon taxes has effectively reduced the grid's dependency by up to 34.7%. Moreover, decreases in storage costs can increase the decline in grid dependency by an additional 18%. Despite the integration of energy storage systems, the ambitious zero carbon target remains unattainable due to the existing installation area constraints of EV charging stations. This study can help policies that align with global efforts to mitigate climate change, enhance energy security, optimize costs, drive technological innovation, and meet increasing demands for sustainable policies.
Keywords: Climate change; Carbon tax; Energy storage; Electric vehicles; Hybrid power systems; Energy consumption; Sustainable development; Automotive engineering; Renewable energy sources; Solar energy; electric vehicle; energy storage systems; hybrid power system; investment cost; self-consumption; POWER-GENERATION; ENERGY-SYSTEMS; STORAGE; DESIGN; OPTIMIZATION; INTEGRATION; INVESTMENT; MODEL; Computer Science; Engineering; Telecommunications